A new species of lizard of the L. wiegmannii group (Iguania: Liolaemidae) from the Uruguayan Savanna - Verrastro, Laura; Maneyro, Raúl; Silva, Caroline M. Da; Farias, Iraia (Zootaxa, 2017)
Lizards of the Liolaemus wiegmannii group comprise 11 species that are widely distributed east of the Andes, occurring in Argentina, Uruguay, and Brazil. Here we analyzed a population of the genus Liolaemus, found in the Pampa region of Uruguay, on isolated sand dunes along the Tacuarembó River. We conducted biometric, meristic, and genetic comparisons between this population and other populations of L. weigmannii from Argentina and Uruguay, and the other species of the L. weigmannii complex. Our morphological and genetic analyses showed that this population represents to a new species of the genus Liolaemus, belonging to the L. wiegmannii group. To date, its known distribution is extremely restricted.